(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Mobile application technologies developing rapidly. There are numerous OS and system available in today’s market. There are three types of main development methods in mobile application, which are Native, Web and Hybrid. These Hybrid mobile app technologies make easy to develop sound mobile application comparable to Native mobile application. These Hybrid mobile app technologies perform better compared to these native mobile app technologies. Hybrid mobile application technology provides flexibility for cross-platform as well as any mobile OS.